The representation of culture in Golden Age Madrid: between attraction and repugnance - Clymer, Camille (2014)
This thesis will examine literary representations of the city of Madrid from the late sixteenth to seventeenth century, with a specific focus on the period of 1600-‐1650. My analysis incorporates a multi-‐genre approach that will include historiography, ephemeral text, festival books, poetry, entremés and prose fiction in order to provide the widest consideration of early modern Madrid through the literature it produced. Several scholars of Golden Age Madrid, such as Garcia Santo-Tomás, Elliott, and Romero-Díaz, have highlighted the need to move away from the static Maravallian dichotomy of power and resistance by which the Baroque has been characterised, and towards an approach that instead examines it from a point of view of its dynamism.